Hypercontractile esophagus resolved after radiofrequency catheter ablation for atrial fibrillation: About a case. Issue 11 (1st June 2020) - Anon, Benjamin; Aubourg, Alexandre; Moussata, Driffa; Babuty, Dominique; Picon, Laurence
Abstract: The pathophysiology of jackhammer esophagus is complex and remains unclear. Radiofrequency catheter ablation is indicated for highly symptomatic and drug‐refractory atrial fibrillation. This technique can induce esophageal and nerve lesions, due to thermal injury. In this report, we describe a case of hypercontractile esophagus diagnosed by HRM (high‐resolution manometry). Esophageal symptoms and HRM normalized immediately after RFCA, and we discuss the pathophysiology of hypercontractile esophagus. Abstract : Case of hypercontractile esophagus diagnosed by High Resolution Manometry and resolved (esophageal symptoms and manometry) immediately after RFCA.